2012
DOI: 10.1016/j.otsr.2012.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Technique and results of endoscopic tenotomy in iliopsoas muscle tendinopathy secondary to total hip replacement: A series of 10 cases

Abstract: IV, retrospective, case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 22 publications
3
38
0
Order By: Relevance
“…The adverse effects of iliopsoas tenotomy are unclear. It is generally thought that there is no significant loss of hip flexion strength after tenotomy [13] . Dora et al.…”
Section: Discussionmentioning
confidence: 99%
“…The adverse effects of iliopsoas tenotomy are unclear. It is generally thought that there is no significant loss of hip flexion strength after tenotomy [13] . Dora et al.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18] Encouraged by the good results reported with endoscopic release for internal snapping hip, similar techniques were used for iliopsoas impingement after THR. Gédouin and Huten 19 reported on 10 cases treated with endoscopic tenotomy, showing complete pain relief in 8 cases and partial pain relief in 2 cases; they concluded that endoscopic tenotomy is a safe and simple technique.…”
Section: E206mentioning
confidence: 99%
“…Blankenbaker et al 38 found one case of iliopsoas tendinopathy in a cohort of 40 patients with snapping hips. Other reports of iliopsoas tendinopathy have been documented in patients with total hip replacements 39,40 with an incidence of 4.3%. 40 The author of this study found no cases of reports in runners, whose prevalence of groin pain is as high as 18 percent.…”
Section: Introductionmentioning
confidence: 95%
“…Other reports of iliopsoas tendinopathy have been documented in patients with total hip replacements 39,40 with an incidence of 4.3%. 40 The author of this study found no cases of reports in runners, whose prevalence of groin pain is as high as 18 percent. 41 Whether it is a rare condition, or under-or misdiagnosed under different names such as tendinitis, bursitis, or snapping hip syndrome, seems unknown.…”
Section: Introductionmentioning
confidence: 95%